PENGARUH SELF EFFICACY DAN DUKUNGAN SOSIAL TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Pangestu, Aji; Ulfah, Maria; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study was set out to determine 1) wheter self-efficacy has an impact on Untan FKIP Economics student"™s drive for entrepreneurship. 2) Does social support have an impact on FKIP Untan Economics Education student"™s enthusiasm for entrepreneurship 3) Does the entrepreneurial motivation of FKIP Untan Economics Education students depend on self-efficacy and social support. This research methodology combines a descriptive and quantitative approach. The investigation's population consisted of 76 Regular Economics A students from the 2018"“2020 class, selected using chance sampling. employed various linear regression analysis methods. The result"™s findings indicated that: 1) self-efficacy, with a t-count of 5.488 , impacts the desire to entrepreneurship t-table 1.993 with 0.000 0.05 significance level. 2) The level of significance 0.250 0.05 and a t count of 1.161 t table 1.993, social support had no effect on entrepreneurial motivation. 3) Social support and selfefficacy affect the motivation of entrepreneurs. Self-efficacy and social support have a 49.1% impact on motivation for entrepreneurship. A significance level of 0.000 0.05 was derived from the SPSS calculation results, indicating the rejection of H0 and the acceptance of Ha. It is determined that entrepreneurial motivation of FKIP Untan students studying economics is influenced by social support and self-efficacy.